2020
DOI: 10.3390/ijms21103570
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and Obesity. Potential Link to Metabolic Disorders and Chronic Complications

Abstract: The World Health Organization (WHO) has recognized obesity as one of the top ten threats to human health. It is estimated that the number of obese and overweight people worldwide exceeds the number of those who are undernourished. Obesity is not only a state of abnormally increased adipose tissue in the body, but also of increased release of biologically active adipokines. Adipokines released into the circulating blood, due to their specific receptors on the surface of target cells, act as classic hormones aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
229
1
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(252 citation statements)
references
References 117 publications
3
229
1
19
Order By: Relevance
“…In addition to the raise in cytokine production, obesity is characterized by increased adhesion molecule levels, which, along with the mentioned cytokines, stimulate tissue-specific macrophage recruitment. Such local inflammation eventually induces IR [ 40 ]. Based on the analytical changes in the chemokine, adipokine and cytokine profiles of obese children, Rivera et al developed a diagnostic tool for IR, rendering a sensitivity and specificity of 93.2%, including levels of leptin, triglyceride:HDL-col ratio, insulin-like growth factor-I (IGF-I), TNFα, monocyte chemoattract protein 1 (MCP1) and pro-fibrotic platelet-derived growth factor (PDGF-BB) [ 41 ].…”
Section: Obesity Inflammation and Oxidative Stressmentioning
confidence: 99%
“…In addition to the raise in cytokine production, obesity is characterized by increased adhesion molecule levels, which, along with the mentioned cytokines, stimulate tissue-specific macrophage recruitment. Such local inflammation eventually induces IR [ 40 ]. Based on the analytical changes in the chemokine, adipokine and cytokine profiles of obese children, Rivera et al developed a diagnostic tool for IR, rendering a sensitivity and specificity of 93.2%, including levels of leptin, triglyceride:HDL-col ratio, insulin-like growth factor-I (IGF-I), TNFα, monocyte chemoattract protein 1 (MCP1) and pro-fibrotic platelet-derived growth factor (PDGF-BB) [ 41 ].…”
Section: Obesity Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Adipose tissue (AT), in addition to its storage functions, is an endocrine tissue that secretes several adipokines and chemokines [ 74 ]. AT also participates in the development of insulin resistance when it is in a state of inflammation known as “low-grade” [ 75 ].…”
Section: S1p Metabolism and Insulin Action: Muscle Liver And Adimentioning
confidence: 99%
“…In a recent study, our group showed an increase in body fat composition after six weeks of therapy using second-generation antipsychotics (SGAs) with a magnitude that depended upon the presence of MetS [ 5 ]. The endocrine functions of adipose tissue are widely known for their ability to produce bioactive peptides and cytokines, or so-called “adipokines,” which regulate metabolism and inflammation and may decrease the insulin sensitivity of tissues [ 6 , 7 , 8 , 9 ]. Chronic, low-grade inflammation during obesity has been established to represent a risk factor for psychiatric disorders [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%